Optimalisasi Komoditas Ekspor Udang Beku Melalui Analisis Korelasi Volume dan Nilai Produksi di PPS Cilacap - Khoerunnisa, Nurani; Aisyah, Aisyah; Fatoni, Khoerul (Jurnal Pasir Laut, 2025)
The fisheries sector is one of the key pillars of Indonesia’s economy, and shrimp is one of its leading export commodities. As the largest export commodity, shrimp contributes significantly to national foreign exchange earnings as well as the welfare of coastal communities. The Cilacap Ocean Fishing Port plays a vital role as a center for fishery activities, including the handling and export of frozen shrimp. However, studies that specifically analyze the relationship between production volume and production value of frozen shrimp exports at the port level remain limited. Understanding this relationship is crucial to optimizing the economic contribution of this commodity. This study aims to analyze the production trends of frozen shrimp for export, assess its contribution to the total fishery exports at Cilacap Oceanic Fishing Port, and measure the relationship between production volume and production value during the period 2020–2024. Data analysis was conducted using Microsoft Excel for trend classification and descriptive statistics, while the Pearson correlation test was applied to measure the linear relationship between the two variables. The results show that the average production volume of frozen shrimp exports was 573.48 tons, with an average production value of USD 6,040,632.27. The highest production volume and value occurred in 2022 (617.43 tons, USD 6,916,008.80), while the lowest occurred in 2023 (527.3 tons, USD 5,256,923.58). The contribution of frozen shrimp to the total export volume at PPS Cilacap reached 21%, while its contribution to export value amounted to 37%. Pearson correlation analysis indicates a very strong relationship between production volume and production value (r = 0.9633 > r-table = 0.878). These findings confirm the strategic importance of frozen shrimp as a key fishery export commodity. Enhancing production and optimizing the value chain are expected to strengthen the competitiveness of Indonesia’s fishery exports.